The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.5530/pj.2018.6.198
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Indigenous Indonesia Medical Plants for Treating Tuberculosis

Abstract: Background: Indonesia is the biggest archipelago country with the second biggest biodiversity in the world. A lot of medical plants for treating various diseases can be found in Indonesia, including medical plants for tuberculosis, an infectious disease caused by Mycobacterium tuberculosis. Objective: The goal of this research is to document the information of Indonesia indigenous medical plants that used various local societies to treat tuberculosis and also analyze active compounds of medical plants with pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…It altered the binding position of FhaA, a ligand of PknB. It might be concluded that these compounds could inhibit the activity of downstream protein target which could suppress the survival and growth of Mtb (Figures 2 and 3) [21].…”
Section: Interaction Between Active Compounds Of Indonesian Medicinalmentioning
confidence: 99%
See 4 more Smart Citations
“…It altered the binding position of FhaA, a ligand of PknB. It might be concluded that these compounds could inhibit the activity of downstream protein target which could suppress the survival and growth of Mtb (Figures 2 and 3) [21].…”
Section: Interaction Between Active Compounds Of Indonesian Medicinalmentioning
confidence: 99%
“…The green line indicates active compound-protein interaction. The red line indicates active compound-active compound interaction [21]. Gray structure, Src wild-type protein; yellow structure, PI3K; green structure, Src-drug complex; pink structure, Src-phytol; blue structure, Src-oleic complex [21].…”
Section: Interaction Between Active Compounds Of Indonesian Medicinalmentioning
confidence: 99%
See 3 more Smart Citations